Retention of service users on opioid substitution therapy in the City of Tshwane, South Africa - Daniela S. Goeieman; Dimakatso S. Nonyane; Doudou K. Nzaumvila; Michelle N.S. anse van Rensburg (AOSIS, 2023)
Background: Opioid substitution therapy (OST) is evidence-based treatment for opioid use disorders and, when taken as maintenance therapy, has proven health and social benefits. The benefits of OST are achieved through the retention of service users in the treatment programme. Aim: To identify factors that affected retention of service users who had OST interrupted in less than 6 months of being in an OST programme. Setting: This qualitative study was conducted with 19 service users from eight Community-Oriented Substance Use Programme (COSUP) sites in the City of Tshwane, Gauteng, South Africa. Methods: Participants were COSUP service users who had interrupted OST in less than 6 months since initiation and were purposefully selected from all COSUP sites. Demographic information was obtained and four focus group discussions covered challenges of OST retention. Discussions were recorded, transcribed and qualitatively analysed using Attride-Stirling's thematic networks framework. Results: The 19 participants were all male, mostly black African, with a mean age of 26 years. Facilitators of retention in OST were individual readiness to change OST accessibility, positive family and peer support, treatment monitoring, understanding and managing expectations of service users, contribution in society and meaningful opportunities for engagement. Barriers were the cost of OST, bureaucracy within the programme, inability to communicate challenges timeously and effectively to treatment providers, boredom, cravings and poverty. Conclusion: Opioid substitution therapy programmes can ensure a holistic approach to prevent and treat harms related to illicit opioid use if they remain person-centred and are well-funded. Contribution: Understanding the barriers to, and facilitators of retention on OST can contribute to improved community-based service delivery.